A study of the acceptance of plantation course in PPKS Mukah / Rebecca Bada - Bada, Rebecca (Universiti Teknologi MARA Sarawak,Kampus Samarahan, 2016)
Since the number of higher education increases, the competitions between both public and private higher education institutions have been increasing. Hence, PPKS Mukah introduces a new course, which is plantation course. Although PPKS Mukah has been offering variety of courses, yet there is no affirmative conclusion as to what factors that contributes to students' acceptance to the courses being offered. Thus, this study is to investigate the factors that influence residents' acceptance to the new course. The results of literature analysis show that there are four group of factors affecting residents' acceptance towards a new course, plantation course: 1) interest 2) family and social 3) industry focus 4) economy. The target of this study is the residents in Mukah-Selangau, Sarawak. The result showed that all variables are reliable.